ANALISIS PENGARUH RISIKO LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN DI INDONESIA - Fani Ramadanti; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the effect of liquidity risk on bank profitability in Indonesia. Liquidity risk in this study is proxied by using factors that can be managed by the bank to avoid the threat of liquidity risk. These factors are LDR, cash reserves, liquidity gap, and NPL. The sample selection using purposive sampling method. Purposive sampling method is a method of sampling based on certain criteria. The sample used in this study are 32 banks. The analysis technique used in this research is multiple linear regression. In addition, the hypothesis test used is the F statistic test and statistical test t. The classical assumption used in this study is multicollinearity, heteroscedasticity test, autocorrelation test, and normality test. The results of the F test states that the deposits, cash reserves, liquidity gap, and NPL jointly affect the ROA. Results of t-test shows that LDR have positive but no significant effect on ROA. Cash reserves have positive and significant effect on ROA. And the liquidity gap and NPL have negative and significant effect on ROA